АДАПТИВНЕ РЕГУЛЮВАННЯ СТРУМІВ СТАТОРА ДЛЯ ПРОЦЕДУР САМОНАЛАШТУВАННЯ АСИНХРОННИХ ЕЛЕКТРОПРИВОДІВ - Пересада , С.М.; Ковбаса, С.Н.; Приступа, Д.Л.; Ляшевський , С.Е. (Інститут електродинаміки НАН України, Київ, 2013)
This paper develops and experimentally substantiates a new algorithm to identify unknown parameters of induction motors during self-commissioning procedure. To guarantee asymptotic identification, we design an adaptive stator current controller using a stator flux observer. Allowed current references guarantee global exponential identification of three induction motor parameters as well as estimation of stator fluxes in both motionless and rotating motor operations. Overestimation of the stator fluxes is introduced to achieve global stability of parameters identification and flux estimation. An asymptotic stator current tracking is also ensured. Our experiments demonstrate that the proposed schemes guarantee identification and estimation accuracy with fast asymptotic convergence of errors to zero. The proposed procedure compliments the existing practical control schemes, and, consistent with vector controls including sensorless algorithms. References 17, figures 4.